Do Countries Compensate Firms for International Wage Differentials? - Ferdinand Mittermaier; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2010)
We address the role of labor cost differentials for national tax policies. Using a simple theoretical framework with two countries competing for a mobile firm, we show that in a bidding race for FDI, it is optimal for governments to compensate firms for international labor cost differentials. Using panel data for western Europe, we then put the model prediction to an empirical test. Exploiting exogenous variation in labor cost differentials induced by the breakdown of communism in eastern Europe, we find strong support for the model prediction that countries with relatively high labor costs tend to set lower tax rates in order to attract mobile capital. Our key result is that an increase in the unit labor cost differential by one standard deviation decreases the statutory tax rate by 7.3 to 7.5 percentage points.
Keywords: H25; H73; F23; 330; foreign direct investment; corporate taxation; labor costs; Arbeitskosten; Lohnstruktur; Direktinvestition; Unternehmensbesteuerung; Steuerpolitik; Europa